2016
DOI: 10.3961/jpmph.16.043
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Economic Evaluation of Telemedicine in Japan

Abstract: Objectives:There is no systematic review on economic evaluations of telemedicine in Japan, despite over 1000 trials implemented. Our systematic review aims to examine whether Japan’s telemedicine is cost-saving or cost-effective, examine the methodological rigorousness of the economic evaluations, and discuss future studies needed to improve telemedicine’s financial sustainability.Methods:We searched five databases, including two Japanese databases, to find peer-reviewed articles published between January 1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 58 publications
1
32
0
1
Order By: Relevance
“…In Japan, remote monitoring and video consultations were found to be generally cost-effective for teledermatology and teleradiology from a provider or societal perspective. However tele-homecare produced mixed results due to lower willingness to pay and higher system costs in areas with public subsidies, which led to overutilization [ 63 ]. In one high-quality review, 74% of included studies found that remote monitoring through mobile devices to support data collection was cost-effective, economically beneficial, or cost saving at base case from a provider or societal perspective [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, remote monitoring and video consultations were found to be generally cost-effective for teledermatology and teleradiology from a provider or societal perspective. However tele-homecare produced mixed results due to lower willingness to pay and higher system costs in areas with public subsidies, which led to overutilization [ 63 ]. In one high-quality review, 74% of included studies found that remote monitoring through mobile devices to support data collection was cost-effective, economically beneficial, or cost saving at base case from a provider or societal perspective [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…eHealth has been proven to be effective in clinical practice [ 1 - 13 , 29 , 30 ]; however, eHealth has not yet been implemented into the working standards of many doctors [ 31 - 33 ]. Prior research indicates that training and education for all those involved with implementation and the use of eHealth is a key factor for the successful incorporation of eHealth [ 13 - 16 , 30 ]. There are various obstacles to implementing eHealth into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 58 systematic reviews showed that overall eHealth provides beneficial results in a wide variety of medical applications [ 12 ]. These developments improve the quality of care or maintain the current standard and reduce health care costs [ 13 - 15 ]. These studies indicate that eHealth would allow for a change clinical practice for the better by using technology.…”
Section: Introductionmentioning
confidence: 99%
“…A utilização da telessaúde perpassa o empoderamento de cada indivíduo e pode ser capaz de reorganizar os sistemas de saúde em monitoramento (16) , eficiência econômica de valor e experiência do indivíduo (17)(18)(19) .…”
Section: Discussionunclassified